Kant, Irrationalism and Religion - Koseni, Merlina (Richtmann Publishing, 2012)
Kant is a philosopher, which dealt with human recognition. He has been considered as an irrationalist. Many philosophers thinkthat he used the irrationalism to justify the trust in religion and to protect the religion from the science. In this paper I shall take a view tothe philosophy of Kant on recongition and to the question if Kant is an irrationalist or not. Did he use the irrationalism to protect thereligion from science? This paper shall show that Kant wasnâ€™t an irrationalist, but he simply tried to determine the limitations of therecognition and to distinguish between what we recongize and what we simply believe. His philosophy of recognition didnâ€™t aim atprotecting the religion from the science. He tells us in some pasages of the book â€œThe critique of pure reasonâ€ that when his theory wouldbe accepted, the men wouldnâ€™t concluded of what they couldnâ€™t know really, and maybe the religion would have some benefits from it.But I think that he meant the trials to prove either the existence of God or the non-existence of God.